Falsa interface como recurso poético na obra interativa - Sogabe, Milton Terumitsu [UNESP] (Escola de Comunicações e Artes da Universidade de São Paulo, 2014)
The concept of false interface is born of the observation and production of interactive installations mediated by digital technology. The false interface is not a technological interface that allows the public to interact with a digital system, but it is a poetic resource, generally an apparatus or craft object with which the public interacts with the artwork, which is a system. The false interface presents a physical relationship, a connection with the technological interface. The playfull audience relates with the false interface and technological interface goes unnoticed in the background, although it captures and send it to the system the public performance.

O conceito de falsa interface nasce da observação e produção de instalações interativas mediadas pela tecnologia digital. A falsa interface não é uma interface tecnológica que permite ao público a interação com um sistema digital, mas é um recurso poético, geralmente um aparato ou objeto artesanal com o qual o público interage com a obra de arte, que é um sistema. A falsa interface apresenta uma relação física, uma conexão com uma interface tecnológica. O público se relaciona ludicamente com a falsa interface e a interface tecnológica passa despercebida, em segundo plano, embora seja ela que capte e envie para o sistema a atuação do público.
False interface as poetic resort in interactive artwork
Keywords: interface; poetics; interactivity; interface; poética; interatividade